Structural deformation of metallic uranium surrounding hydride growth sites. (July 2015) - Jones, Christopher P.; Scott, Thomas B.; Petherbridge, James R.
Highlights: UH3 formation on uranium surfaces by a controlled uptake of hydrogen at 240 °C. Large hydride growths (35–125 μm in diameter) form at the surface. Confined hydride expansion during growth generates stress in the subsurface. EBSD scans found micro-cracking and twins as forms of stress relief in the metal. Abstract: Electron backscatter diffraction (EBSD) was utilised to probe the microstructure of uranium metal in the vicinity of surface corrosion pits, resulting from hydrogen exposure (5 × 10 4 Pa, at 240 °C). Microstructural analysis of the surface revealed a subtle increase of grain orientation variation for grains at the border of the hydride growths. Cross sectional analysis, at pit sites, revealed significant microstructure deformation in the form of crystal twinning and micro-cracking beneath the surface. These observations provide qualitative evidence that local stress intensities generated as a consequence of hydride growth and confinement, were sufficient to cause deformation within the parent metal.